Evaluation of the Duties and Preparations of Local Governments for Chemical Biological Radioactive Nuclear Hazards - Karayünlü, Gökhan (The Bulletin of Legal Medicine, 2025)
Objective: This study aims to examine the preparedness and practices of local governments against Chemical, Biological, Radiological, and Nuclear (CBRN) hazards and to offer relevant recommendations. The research is grounded in data gathered through descriptive analysis, consistent with the qualitative research paradigm.Method: The study was conducted through a literature review on CBRN concepts and an examination of the regulations and preparedness measures of local governments and their affiliated units regarding actual and potential hazards. Official documents, institutional regulations, and field practices were analyzed to assess current capacities and coordination mechanisms.Results: The study revealed that institutions in Türkiye operating in the CBRN field act in line with national authorities such as AFAD, the Turkish Atomic Energy Authority, and the Ministry of Health. It was found that Fire Departments within local governments have varying levels of preparedness, and differences exist among provinces in terms of field practices. Coordination among institutions during CBRN events is regularly tested through the Turkey Disaster Response Plan Exercises, which contribute to updating institutional regulations and improving overall response capacity.Conclusion: Although inter-institutional coordination in response to CBRN incidents has improved, certain challenges remain. These include delays stemming from the ambiguity in identifying the type of threat, determining the appropriate intervention method, and clarifying authority transfer procedures in hot zones. Addressing these issues is essential for effective disaster response and public safety.
Keywords: CBRN; CHEMİCAL; BİOLOGİCAL; Radioactive; Nuclear; Local Government